(untitled) (Journal of the College of Languages (JCL), 2014)
The dictionary meaning of the word is a linguistic category of the thing in a specific way . it is also a brief description of it .The main function of the concept lies in the total scientific reflection of the things where as the main function of the meaning is a brief reference to a certain content (extralinguistic ) which shows human knowledge . The meaning is (a storage unit ) of knowledge of the world ,but this does not give the extra linguistic meaning which the old words have . Hence, additional cultural ,ethnic,communicative and genetic information is needed. All the old words which are brought into use are divided into two groups: The first involves the words that indicate all the phenomena and things which are brought into use again. Some of which are concerned with resent economic life and others are concerned with some aspects of life before the October Bolshevic Revolution . The second group contains all the phenomena and the old things which are used in the modern Russian language and have similarity with the old facts .